The Effect of Ecological and Physiological Adaptation of Food Crops on Food Security in the Banyumas Highlands Region - Kartika Eka Wijayanti; Altri Mulyani; Syahrul Ganda Sukmaya; Sifa Aulia Wicaksari; Wahyu Adhi Saputro (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to analyze the influence of ecological and physiological adaptations of food crops on food security in the highland area of Banyumas Regency. The research area includes Baturaden, Kedungbanteng, and Cilongok Districts, which are known to have a surplus of rice food reserves. Ecological adaptation includes how food crops adapt to specific environmental conditions at high altitudes, while physiological adaptation includes plant responses to factors such as temperature, humidity, and soil type. The data used in this study came from the Central Statistics Agency of Banyumas Regency in 2021. The results show that food accessibility, measured through physical and social access, has a significant correlation with food security. Physical and social access were significantly correlated with food security, with significance values of 0.046 and 0.017, respectively. The study concluded that the ecological and physiological adaptations of food crops play an important role in supporting food security in the Banyumas highlands, and that increased physical and social accessibility can improve food security stability in the region. Local governments need to focus on providing facilities and infrastructure that support food accessibility to ensure sustainable food security in the highlands.